Analisis Pertimbangan Hakim Mahkamah Agung Dalam Mengadili Permohonan Kasasi Penggelapan - Betty Kusumaningrum; Edy Herdyanto., S.H., M.H (Sebelas Maret University, 2017)
This research aims to find out what is the basis for consideration of Supreme Court for granted and rejected an cassation in the case of embezzlement in the decision of the Supreme CourtNumber: 373 K/Pid/2015, wasin accordance with the requirements of formal and the terms material of the Criminal Procedure Code. This research is a study of doctrinal in a way to the law primary and secondary. The technique of collecting material law in this paper is the study of literature that is the collection of legal materials through material written law. The analysis of the legal materials conducted by the deductive method and drawn the conclusion to construct arguments. Based on the results of research and discussions are produced, it can be concluded that in the case of embezzlement of trademark righta committed by the defendant Soeharso, consideration of the Supreme Court in examining and deciding an cassation by prosecutors against the verdict free from any lawsuits High Court of Semarang on appeal in compliance with the provisions of the Criminal Procedure Code. (Keyword : Legal Considerations, The Supreme Court, Embezzlement)